Johannes Widmanns "Behende und hubsche Rechenung" : die Textsorte "Rechenbuch" in der Frühen Neuzeit - Gärtner, Barbara (Free online access: JSTOR., 2000)
The German Linguistic Studies Series is a comprehensive and outstanding forum in its field. It has borne the name of its subject in its title since the foundation of the series in the eighth decade of the last century.The series is comprehensive in the broad spectrum of topics covered (language levels, varieties, communication forms, epochs) in the range of research perspectives (theoretical and empirical studies, fundamental research and applications, interdisciplinarity with psychology, the social sciences etc.) and methodologies (the sole criterion is quality), in the rhythm of research (tr.